168k views
0 votes
Please help with answer below:

Please help with answer below:-example-1

1 Answer

1 vote

9514 1404 393

Answer:

  • c = 7
  • d = 5

Explanation:

When a value is moved from outside the radical to inside, it gets an exponent equal to the index of the radical.

A) x³√x = √(x^(2·3+1)) = √(x^7) . . . . c = 7

__

B) x∛(x²) = ∛(x^(3·1+2)) = ∛(x^5) . . . . d = 5

_____

Alternate solution

You could use the fractional exponent equivalent of the radical and write the sum of exponents equation.

A) c/2 = 3+1/2 ⇒ c = 7 . . . . . exponents for x

B) d/3 = 1+2/3 ⇒ d = 5 . . . . . exponents for x

__

The exponent rules being used here are ...

√x = x^(1/2)

∛x = x^(1/3)

(x^a)(x^b) = x^(a+b)

(x^a)^b = x^(ab)

User YUKI
by
5.5k points